Large Adiabatic Temperature Change in Magnetoelastic Transition in Ni50Mn35Cr2Sn13 Heusler Alloy of Granular Nanostructure - H. R. Prakash; S. K. Sharma; S. Ram; S. Chatterjee (Advanced Aspects of Engineering Research Vol. 9, 2021)
A ternary Ni-Mn-Sn Heusler alloy – eco-friendly energy material presents a granular nanostructure, a pioneering series of magnetocaloric materials of a huge heat-energy exchanger in a synergic magnetoelastic transition. A small additive of nearly 2 at% Cr effectively tunes a valence electron density of 8.090 electrons per atom and a duly large change in the entropy \(Δ\)SM\(\)A = 4.428 J/kg-K (\(Δ\)SM\(→\)A = 3.695 J/kg-K in the recycle) at the martensite \(\) austenite phase transition, which is useful for the magnetic refrigeration and other cooling devices. The Cr additive - a grain refiner promptly tempers the tetragonality with an aspect ratio c/a = 0.903 of the low temperature martensite phase, so as it exhibits a promptly tailored adiabatic temperature change of 10 K. At room temperature, the sample exhibits a narrow ferromagnetic hysteresis loop, with 48.9 emu/g saturation magnetization and 82.1 Oe coercivity, useful for domestic usages.